A Critical Evaluation of Public Participation in the Sudanese Planning Mandates (University of Khartoum Engineering Journal, 2022)
In the last four decades, the concept of community participation is increasingly getting attention in most of the world. While there is quite extensive literature on the concept itself, the process of community participation evaluation still lags behind. The necessity to improve community participation requires understanding the context where plans are formulated, developed, approved and implemented. This context is guided by three main elements including; planning mandates and by laws; planners’ perception about community participation; and the actual planning practiced by planning institutions. Using Cohen and Uphoff three dimensions of participation as a benchmark, this article includes analysis of the extent to which planning mandates in Sudan provide guidance for planners in terms of what is participation and how and when to involve citizens in the planning process. This analysis was achieved through extensive literature reviews and critical study and analysis of planning mandates between 1950 and 2000. The conclusions drawn by this article show that planning mandates in Sudan have addressed the issue of Community Participation apprehensively in a very informative nature, the process of involving citizens in the planning process "as mandated" focus on area re-planning much more than urban/city planning. Equally, involving citizens as mandated occurs in the less important stages of planning.